Reorganization of the endoscopic activity of Cancer Institutes during phase II of the Covid-19 emergency. Issue 11 (November 2020) - Fiori, Giancarla; Trovato, Cristina; Staiano, Teresa; Magarotto, Andrea; Stigliano, Vittoria; Masci, Enzo; Ciuffi, Mario; Rossi, Giovanni Battista; Fantin, Alberto; Realdon, Stefano; Ugenti, Ippazio; Cannizzaro, Renato
Abstract: After the lockdown during the emergency phase of the Covid-19 pandemic, we have to deal with phase 2, a period of uncertain duration, with a controlled and progressive return to normalization, in which we need to reconcile our work and our movements with the presence of the virus on our territory. Digestive endoscopic activity is a high-risk transmission procedure for Covid-19. The measures put in place to protect healthcare personnel and patients are stressful and "time-consuming" and lead to a reduction in the number of endoscopic procedures that can be performed. In this scenario, the Oncological Institutes are forced to make a rigorous selection of patients to undergo endoscopic examinations and treatments, according to lists of exceptional priorities, in order to guarantee cancer patients and subjects at high risk of developing digestive tumors, a preferential diagnostic and therapeutic process, protected from contagion risks. For this purpose, cuts and postponing times of endoscopic performances are here proposed, which go beyond the guidelines of scientific societies and have little evidences in the literature. These changes should be applied limited to this exceptional period and in proportion to the capacity of each operating unit in order to meet the demands of the patients.